2015
DOI: 10.1515/bot-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Does bryozoan colonization alter the biochemical composition of Saccharina japonica affecting food safety and quality?

Abstract: The encrusting bryozoan Membranipora membranacea frequently colonizes late-harvested blades of the cultured Saccharina japonica. We measured the proximate compositions, amino acid and fatty acid profiles and metal contents of bryozoans, colonized blades and healthy blades. Bryozoans contained high levels of crude ash (657 g kg -1 dry weight) and arsenic (As; 49 mg kg -1 dry weight) contents, exceeding the recommended range for human food, and had relatively low levels of essential amino acids. The content of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The sharp increase in protein content to almost 20% of DW at two locations in our study (2-60°N and 6-63°N) from June onwards was probably due to fouled biomass, the protein originating from epibionts and not from the kelp itself. M. membranacea, the main fouling epibiont at these locations, has a high protein content (> 15% of DW on cultivated Saccharina japonica, Getachew et al 2015). It has also been suggested that a higher protein content found in kelp at deeper waters is a result of reduced light exposure (Cronin and Hay 1996;Ak and Yücesan 2012;Sharma et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The sharp increase in protein content to almost 20% of DW at two locations in our study (2-60°N and 6-63°N) from June onwards was probably due to fouled biomass, the protein originating from epibionts and not from the kelp itself. M. membranacea, the main fouling epibiont at these locations, has a high protein content (> 15% of DW on cultivated Saccharina japonica, Getachew et al 2015). It has also been suggested that a higher protein content found in kelp at deeper waters is a result of reduced light exposure (Cronin and Hay 1996;Ak and Yücesan 2012;Sharma et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The differences between faunal assemblage composition of frond samples from different months and years for the seeded treatments and high and low density treatments for the artificial samples were compared using multivariate tests. A Simpson's dissimilarity matrix was generated from the presence/ absence data for the 6 seeded sampling dates (April, May andJune, 2014 and2015) and the 2 artificial treatments separately using the PopTools (Hood 2014) add-on in Excel. Simpson's dissimilarity has the advantage that it only measures the turnover of species and is not affected by changes in species rich ness between samples (Baselga 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis can be decreased as fouling organisms can create a barrier to nutrient uptake (Hurd et al 2000), can block the surface area of the frond (Hepburn et al 2006) and restrict light availability (Cancino et al 1987). In addition, heavily fouled fronds have a lower market value as they are considered to be unsuitable for human consumption due to a degradation of taste and quality (Park & Hwang 2012, Peteiro & Freire 2013b, Getachew et al 2015. Lower-value fronds are instead used for animal feed (Bruton et al 2009) and severely fouled fronds are discarded (Peteiro & Freire 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Biofouling is one of the major challenges and constraints in the development and growth of the seaweed aquaculture sector (Getachew et al 2015;Lüning and Mortensen 2015;Stévant et al 2017;Bannister et al 2019). Effects of biofouling include the loss of commercial value (Park and Hwang 2012), decrease in productivity due to breaking fronds (Dixon et al 1981;Krumhansl et al 2011), and reduced growth due to limited nutrient uptake (Hurd et al 2000) and restricted light availability (Cancino et al 1987).…”
Section: Introductionmentioning
confidence: 99%